Pharmacodynamics of Trovafloxacin, Ofloxacin, and Ciprofloxacin against Streptococcus pneumoniae in an In Vitro Pharmacokinetic Model - Lister, Philip D. (American Society for Microbiology, 1999)
An in vitro pharmacokinetic model was used to simulate the pharmacokinetics of trovafloxacin, ofloxacin, and ciprofloxacin in human serum and to compare their pharmacodynamics against eight Streptococcus pneumoniae strains. The MICs of ofloxacin and ciprofloxacin ranged from 1 to 2 μg/ml. Trovafloxacin was 8- to 32-fold more potent, with MICs of 0.06 to 0.12 μg/ml. Logarithmic-phase cultures were exposed to peak concentrations of trovafloxacin, ofloxacin, or ciprofloxacin achieved in human serum after 200-, 400-, and 750-mg oral doses, respectively. Trovafloxacin was dosed at 0 and 24 h, and ofloxacin and ciprofloxacin were dosed at 0, 12, and 24 h. Human elimination pharmacokinetics were simulated, and viable bacterial counts were measured at 0, 2, 4, 6, 8, 12, 24, and 36 h. Trovafloxacin was rapidly and significantly bactericidal against all eight strains evaluated, with viable bacterial counts decreasing at least 5 logs to undetectable levels. Times to 99.9% killing were only 1 to 3 h. Although the rate of killing with ofloxacin was substantially slower than that with trovafloxacin, ofloxacin was also able to eradicate all eight strains from the model, despite a simulated area under the inhibitory curve/MIC ratio (AUC/MIC) of only 49. In contrast, ciprofloxacin eradicated only five strains (AUC/MIC = 44) from the model. Against the other three strains (AUC/MIC = 22), the antibacterial activity of ciprofloxacin was substantially diminished. These data corroborate clinical data and suggest that trovafloxacin has a pharmacodynamic advantage over ciprofloxacin and ofloxacin against S. pneumoniae in relation to its enhanced antipneumococcal activity.